2016
DOI: 10.18869/acadpub.jafm.68.235.24575
|View full text |Cite
|
Sign up to set email alerts
|

Darcian Natural Convection in Inclined Square Cavity Partially Filled Between the Central Square Hole Filled with a Fluid and Inside a Square Porous Cavity Filled with Nanofluid

Abstract: The problem of darcian natural convection in inclined square cavity partially filled between the central square hole filled with fluid and inside a square porous cavity filled with nanofluid is numerically studied using the finite element m ethod. The left vertical wall is maintained at a constant hot temperature T h and the right vertical wall is maintained at a constant cold temperature T c , while the horizontal walls are adiabatic. The governing equations are obtained by applying the Darcy model and Boussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The thermal conductivity and viscosity of nanofluid models have been calculated using Eq. (17-18) which had been used by many researchers like [39, [61][62][63][64][65][66][67][68][69][70][71][72]:…”
Section: Figure 1 Schematic Diagram Of the Problemmentioning
confidence: 99%
“…The thermal conductivity and viscosity of nanofluid models have been calculated using Eq. (17-18) which had been used by many researchers like [39, [61][62][63][64][65][66][67][68][69][70][71][72]:…”
Section: Figure 1 Schematic Diagram Of the Problemmentioning
confidence: 99%
“…They noticed that the existence of nanomaterials within the cavity led to a decline in the heat transfer rate due to their increased dynamic viscosity, and thus, it could be useful for nanofluid applications that required improved dielectric or antibacterial properties. Alsabery et al. (2016) used an oblique porous cavity to study the free convection of a working nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they confirmed that the Nusselt number has been significantly positively affected by the Darcy number, especially at the high value of the Darcy number, as it has shown a noticeable increase. Another group by Alsabery et al. (2016) used the GFEM to model the free convection behavior inside two inclined concentric square cavities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural heat transfer through cavities saturated with heat generating porous media is widely investigated due to its extensive applications in the fields of thermal and geothermal energy, heat convection management (due to buried atomic wastes), combustion technology, porous catalysts, soil pollution, exothermic reactions inside porous reactors and fuel cells performance enhancement (Rashidi et al , 2012; Pop et al , 2016; Alsabery et al , 2016; Sheremet and Pop, 2015; Rashad et al , 2017; Sun and Pop, 2013; Alsabery et al , 2017; Sheikholeslami et al , 2015). Likewise, there is a novel concept known as nanofluids introduced by Choi and Eastman (1995) has gained a great deal of attention in a wide range of studies to enhance heat transfer rate by higher thermal conductivity of nanofluids compared to the base fluid.…”
Section: Introductionmentioning
confidence: 99%